Efeitos da fotobiomodulação sobre o reparo neuromuscular em lesão nervosa periférica - Santos, Lucas Andreo Dias dos (2020)
Introduction: Peripheral nerve injury (PNI) can lead to a negative effect on quality of life because there is no complete reaction from motor or sensory disturbances. The treatment with photobiomodulation (PBM) had its positive results in the treatment of PNI, specifically with regard to the reduction of recovery time, although its mechanisms of action are still not well founded in the literature. Objective: To analyze the effects of PBM on neuromuscular repair. Methodology: A bibliographic search was carried out in the following databases: PubMed / MEDLINE, Digital Library SCOPUS and SPIE, for original articles published in January of 2007 to March of 2016 on the use of LLLT in experimental models of PNI. In vitro production was performed on Schwann cells, lineage ST88-14 for analysis of cell viability, morphology and gene expression. For the experimental model of PNI it was used 85 Wistar rats which were analyzed at 1, 2, 3 and 4 weeks. PNI was achieved by crushing the left sciatic nerve. Laser treatment (780nm, 0.04 cm², 3.2 J) was realized over the nerve (20J/cm², 0.8 J per point in 4 points) and/or tibialis anterior muscle (10 J/cm², 0.4 J per point in 8 points). Results:18 original articles were selected that demonstrated the effects of PBM on the acceleration of functional recovery, on the morphological aspects and on the modulation of the expression of inflammatory cytokines and growth factors. In the in vitro studies PBM promoted an increase in metabolic activity, cell migration and cell cycle without altering cell viability, presenting different results according to the dosimetric parameters. The PBM promoted an improvement of the functional aspects evaluated with regard to gait analysis, mechanical hyperalgesia and muscle mass, besides promoting an increase in the diameter and CSA and, gene modulation in the post LNP muscles, presenting better results when applied in a combined method.